2019
DOI: 10.5539/elt.v12n10p29
|View full text |Cite
|
Sign up to set email alerts
|

Increasing ELL Parental Involvement and Engagement: Exploration of K-12 Administrators in a Rural State

Abstract: This study reports the findings from an exploration of K-12 administrators in a rural state about how they can more effectively engage and involve families of English language learners (ELLs). The guiding questions for this study are: (1) How does the role of administrators influence the engagement and involvement of ELL parents within K-12 education? (2) What can administrators do within their districts specific to their district in order to facilitate ELL parental engagement and involvement? Through an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…In addition, it was revealed that the way the teacher cooperated with them, helping them to feel welcomed at school and facilitating their children"s successful learning, empowered parents" role unresponsively to their previous background knowledge on language learning. The aforementioned findings are consistent with those of previous studies (Hoover-Dempsey & Sandler, 2005;Goodall & Vorhaus, 2011;Paik, et al, 2019;Parsons & Shim, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, it was revealed that the way the teacher cooperated with them, helping them to feel welcomed at school and facilitating their children"s successful learning, empowered parents" role unresponsively to their previous background knowledge on language learning. The aforementioned findings are consistent with those of previous studies (Hoover-Dempsey & Sandler, 2005;Goodall & Vorhaus, 2011;Paik, et al, 2019;Parsons & Shim, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…An increasing interest in launching effective FL (foreign language) learning programs in preschool settings (Murphy, 2014;Rixon, 2013) has resulted in research examining the role of parental involvement in children"s language development and their education (Driessen, 2019;Epstein, 2011;Garbacz, et al, 2015;Gaynor, 2012;McDowall, Taumoepeau & Schaughency, 2017;McWayne, Manz, & Ginsburg-Block, 2015;Vellymalay, 2012). Home literacy environment has been recorded as one of the most significant predictors related to early literacy skills (Hume, Lonigan, & McQueen, 2015;Niklas, Tayler, & Schneider, 2015), while parental involvement in school activities is also associated with significant benefits for children's school success and their overall development (Bempechat & Shernoff, 2012;Gordon & Cui, 2012;Paik, et al, 2019;Parsons & Shim, 2019;Wang & Sheikh-Khalil, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests the need to better understand how enrollment of ELL students may be related to consistent assessment. It would be useful for researchers to examine ELL enrollment in rural schools and how the assessment and implementation of PBIS in rural schools is integrating recommendations for supporting ELL students in rural schools, such as family–school collaboration in support of ELL student learning and social behavior goals (Barrio, 2017; Parsons & Shim, 2019). Thus, researchers might interview parents, students, and school professionals to better understand parents’ reasons for leaving a school and the school systems and practices in place to support ELL students and their families.…”
Section: Discussionmentioning
confidence: 99%